Five undescribed species of Corynespora - and KAMAL, NIDHI SHARMA, R.K. CHAUDHARY (Indian Phytopathology, 2002)
Five hitherto undescribed fungal species collected from forests in North Eastern Uttar Pradesh. collected on hosts belonging to four different families have been described and illustrated. These are C. premnigena and C. catenulata on leaves of Premna mucronata and Clerodendrum indicum (Verbenaceae) respectively, C. azadirachtiana on Azadirachta indica (Meliaceae), C. colebrookiana on Colebrookia oppositifolia (Lamiaceae) and C. barleriicola on Berlerie cristata (Acanthaceae).